Análise experimental de diferentes configurações de termossifões para aplicação em coletor solar - Espirito Santo, Michel do (2017)
Solar collectors assisted by thermosyphons or also called vacuum solar collectors, are viable alternatives for the use of water heating and act directly on a significant portion of the energy consumption. They are more efficient, operate at higher temperatures, and can be more compact compared to conventional solar collectors. In this Master's Dissertation are presented the design and the experimental tests of three different configurations of thermosyphons applicable in solar collectors, denominated thermosyphons of the Type # 1, Type # 2, and Type # 3. Also, the best configuration is analyzed in an experimental bench in the form of a prototype of solar collector assisted by seven thermosyphons for application in domestic water heating. Firstly, the theoretical analysis was made from the operational limits of the thermosyphons, which indicate the maximum amount of energy in the heat form that the device transfers under certain operating conditions. For this determination, a computational code was elaborated using Engineering Equation Solver (EESTM) software. From this analysis and preliminary experimental tests, it was identified that the thermosyphon of the Type # 3 was the one that demonstrated the best results of thermal resistance and operating temperature in the different flow rates and inclinations analyzed. In the prototype of the solar collector assisted by thermosyphons, the seven thermosyphons had behaviors very close to that verified in the thermosyphon Type # 3 analyzed individually, proving that this is the characteristic behavior of this configuration. In the efficiency analysis, the prototype of the solar collector obtained values between 60% and 90%, results greater than that of a conventional solar collector, which is 30%. After this study, it was possible to identify that the use of thermosyphons in solar collectors is a highly feasible alternative for the energy saving applied to domestic water heating.